2018
DOI: 10.1007/s13304-018-0536-2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of hepatic metastases from gastric cancer

Abstract: The purpose of the study was to investigate the clinical factors influencing the prognosis of patients submitted to hepatectomy for metastases from gastric cancer and their clinical role. We conducted a retrospective multicentre review. We evaluated how survival from surgery was influenced by patient-related, tumour-related and treatment-related prognostic factors. We analysed data on 144 patients submitted to hepatectomy for metastases from gastric cancer, in the synchronous and metachronous setting. In 117 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 24 publications
0
20
1
Order By: Relevance
“…In 1994, one of the first studies on the subject[ 22 ] showed how the presence of serous invasion of gastric cancer was a determining prognostic factor in the resection of synchronous hepatic metastases. Since then, T stage has been extensively investigated[ 8 , 14 , 23 - 31 ]. Serous invasion is the first step in metastatic spread to the peritoneal cavity, an unfavorable prognostic factor[ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 1994, one of the first studies on the subject[ 22 ] showed how the presence of serous invasion of gastric cancer was a determining prognostic factor in the resection of synchronous hepatic metastases. Since then, T stage has been extensively investigated[ 8 , 14 , 23 - 31 ]. Serous invasion is the first step in metastatic spread to the peritoneal cavity, an unfavorable prognostic factor[ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, in their trial, Fujitani and colleagues did not consider the possibility of a complete surgical resection of both gastric cancer and metastases, limiting their comparison between chemotherapy alone versus gastrectomy plus chemotherapy in the metastatic setting. The recent literature [6][7][8][9][10][11][12][13][14][15] contrasts with the conclusion of the REGATTA Trial, showing that an integrated multidisciplinary approach including chemotherapy and surgery may offer, at least to a selected subgroup of patients, unexpected results, in particular when a radical (R0) resection can be achieved both on gastric primary and metastases. Although the power of these studies is limited by their retrospective nature, they cannot be ignored, particularly in the light of results achieved by conversion therapy.…”
Section: Introductionmentioning
confidence: 93%
“…Our previous studies [6,[9][10][11] focused on hepatic metastases and endorsed an aggressive integrated approach including surgery for selected patients, on the theoretical assumption that hepatic metastasis may still characterize a regional and not a systemic disease, and thus display a better prognosis, since the liver plays a "first-filter" role for the portal bloodstream. Unexpectedly, however, expanding our evaluation to the entire cohort of metastatic patients, we did not observe better survival outcomes for patients with hepatic metastases when compared to those presenting metastatic disease in the peritoneal cavity, distant lymph nodes, extra-hepatic haematogenous locations, or any possible association of the above.…”
Section: Metastatic Site Does Not Influence Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…For mRCC, such studies have also been presented (though without mentioning if isPM observations were included), which unanimously confirmed that the initial total tumor burden was a negative prognostic factor (231,(251)(252)(253). Metastases surgery also proved that the time of occurrence of metastases was a prognostic factor, e.g., in liver metastases surgery of colorectal cancer (248,254,255), gastric cancer (256), and breast cancer (257). After all, these parameters were also risk factors proven in RCC surgery (232, 233, 258-261), as well as in RCC metastases surgery (262)(263)(264)(265)(266)(267)(268), although the significance of these factors varied greatly depending on individual properties of primary RCC and metastasis localization and not all factors were equally effective for every metastatic localization.…”
Section: Ineffectiveness Of Risk Factorsmentioning
confidence: 79%